Reply to Timothy Hinton on Gareth Moore's Philosophy of God. (11th November 2020) - Robinson, Howard
Abstract: Hinton's defence of Gareth's philosophy is welcome ‐ but I don't think it works. This is because he does not show how, on Gareth's theory, 'God' can be referential, and, if it is not referential, then 'belief in God' cannot be taken in any literal sense. Sadly, I stand by my original claim that the radical, Phillipsian Wittgensteinianism that Gareth adopts is a form of informal positivism that only allows an expressivist sense to religious, and, indeed, all metaphysical language.